PENYULUHAN DAN PENERAPAN INOVASI PENGOLAHAN SUSU SAPI MENJADI SABUN SUSU DAN SUSU PASTEURISASI DI KELOMPOK TANI DAN TERNAK MARGO UTOMO PILAHAN KABUPATEN SEMARANG - Yunita Khusnul Khotimah; Fithrotun Nafisa, Al Dilla; Khasanah, Uswatun; Suryani, Hasna Fajar (Jurnal Indonesia Mengabdi, 2025)
The application of innovations in processing cow's milk into milk soap and pasteurized milk was carried out at the Kelompok Tani dan Ternak Margo Utomo Pilahan, Semarang Regency, as a step to improve farmers' knowledge and skills in converting livestock products into products with added value. The program began with a needs survey, followed by training using presentation, discussion, and practical demonstration methods of making pasteurized milk and soap from milk. During the program, participants received materials in an interactive way and were directly involved in the process of making processed products. The assessment results indicated an increase in participants' understanding and ability in milk processing, as well as a growing enthusiasm to develop a dairy-based business within the group community. This activity proved successful as an answer to the problem of excess milk production among farmers and has the potential to encourage increased income and economic independence of the community.